IMPORTANȚA EDUCAȚIEI RELIGIOASE ÎN CONTEXTUL CRIZELOR MONDIALE (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2024)
The importance of religious education in the context of global crises.This article presents the importance of religious education, the roles of the family and the school which are fundamental tools for reducing world crises. Religious education is a means by which people with integrity are formed, who are open to tolerance and mutual respect, being concerned with the continuous improvement of their relations with the divinity and with fellow human beings. These are some of the goals religious education is looking to achieve.